Violence in scripture - Creach, Jerome F. D. (Jerome Frederick Davis), 1962- (2013)
"The Bible frequently depicts God as angry and violent, and also sometimes depicts human violence as positive or even as commanded by God. This forms one of the most vexing problems in approaching Scripture and in interpreting the Bible for preaching and teaching today. In this volume, Creach first examines the theological problems of violence and categorizes the types of violence that appear in scripture. Then, he wrestles with the most important biblical texts on violence to work through specific interpretational issues. This new volume in the Interpretation: Resources for Use of Scripture in the Church series will help preachers and pastors interpret those difficult texts, encouraging them to face violence in the Bible with honesty"--
Includes bibliographical references (pages 241-260) and indexes
Keywords: Violence in the Bible; RELIGION / Biblical Criticism & Interpretation / Old Testament; RELIGION / Biblical Studies / Old Testament